Penguatan Institusi sebagai upaya Percepatan Pengentasan Kemiskinan Ekstrem pada Wilayah Perdesaan di Kabupaten Nagan Raya - Sailal Arimi; Harmaini Harmaini; Yasrizal Yasrizal (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2025)
This Community Service (PKM) is motivated by various studies that explain that weak institutions at the village level in poverty alleviation have contributed to the failure of extrem poverty alleviation efforts so that rural areas in Indonesia are still the national poverty barn. Strengthening institutional elements such as rule of law, regulatory quality, transparency, government effectiveness and control of corruption can be key instruments to succeed in the poverty alleviation agenda in rural areas. The PKM activity in Alue Waki ​​Village, Darul Makmur District, Raya Regency aims to increase knowledge and understanding in order to encourage dynamic cooperation between the government, private sector, and civil society in managing public resources to determine the direction of development, especially in terms of poverty alleviation. The method used is this activity is a participatory learning method through the delivery of several materials on poverty and institutional strengthening which is followed by discussion and questions and answers about the importance of the existence of strong institutions in poverty alleviation. The results of this community service implementation are expected to encourage the strengthening of institutions in the village for the success of poverty alleviation efforts.